Laporan Kasus: Penanganan Dipylidiasis pada Kucing Anggora dengan Praziquantel - Annisa Putri Cahyani; I Nyoman Suartha; Nyoman Sadra Dharmawan (Jurnal Sains dan Teknologi Peternakan, 2019)
Dipylidiasis is a tapeworm disease that attacks cats and dogs and classified as a zoonotic disease because it can be transmitted to humans. A 2 years old female angora cat weighing 3 kg was examined with complaints of bloody diarrhea for 2 weeks. The results of native faecal examination showed the presence of D. caninum worm eggs. Animals diagnosed with dipylidiasis. Cat cases were treated by administering 50 mg praziquantel therapy with the recommendation of 1 tablet for 10 kg/BW orally. In conclusion, the treatment of dipylidiasis by administering praziquantel therapy has proven to be effective.